(untitled) (Nativa, 2024)
ABSTRACT: The aim of this study was to analyse the existence of floristic groups in Seasonal Semi-deciduous Forest fragments under the effects of selective logging located in Tapurah-MT. The given clusters were allocated and measured, and each one had five subunits of 500 m². For each sampling unit, all of the arboreal and shrub species with a diameter at breast height (DBH) equal to or greater than 10 cm were considered. In the sampling subunits studied, the vegetation matrix was composed of the density of the 20 species in the fragment with the greatest importance. The presence of floristic groups was verified by a grouping analysis through the species association method. Euclidean distance with Hellinger’s transformation was used as a similarity measure between the groupings, and Ward’s linking method was used for the dendrogram elaboration. The number of groups was established by Kendall’s coefficient, and correlations between the groups and the species were assessed. Once the concordance was determined, the number of groups in which the species were correlated was chosen. The species’ auto-ecological characteristics, mainly the propagating material dispersion type and average DBH, were the main factors responsible for the species association and similarity inside each floristic group. Keywords: similarity between species groups; species association; floristic group; environmental disturbance. Análise de agrupamento de fragmento florestal sob efeitos da extração seletiva no bioma amazônico RESUMO: O objetivo deste estudo foi analisar a existência de grupos florísticos em fragmentos de Floresta Estacional Semidecidual sob os efeitos da exploração madeireira seletiva localizada em Tapurah-MT. Os transectos foram subdivididos em cinco subunidades de 500 m². Para cada unidade amostral, foram consideradas todas as árvores com DAP maior ou igual a 10 cm. Nas subunidades amostrais estudadas, a matriz de vegetação foi composta pela densidade das 20 espécies de maior importância no fragmento. A presença de grupos florísticos foi verificada por meio de uma análise de agrupamento pelo método de associação de espécies. A distância euclidiana com a transformação de Hellinger foi usada como uma medida de similaridade entre os agrupamentos, e o método de ligação de Ward foi usado para a elaboração do dendrograma. O número de grupos foi estabelecido pelo coeficiente de Kendall e as correlações entre os grupos e as espécies foram avaliadas. Uma vez determinada a concordância, optou-se pelo número de grupos em que as espécies estavam correlacionadas. Foi verificado que as características auto-ecológicas das espécies, principalmente o tipo de dispersão do material propagado e o DAP médio, foram os principais responsáveis pela associação e similaridade das espécies dentro de cada grupo florístico. Palavras-chave: similaridade entre grupos florísticos; associação de espécies; agrupamentos florísticos; perturbação ambiental.